A study of coleopteran walking gait and electrical stimulation of its middle leg - Mohamed Fareez Aziz (2014)
This report aims to provide information on the project of Cyborg Insect Walking Machine. The project involves the inducing of electrical current to perform muscle stimulation on a live beetle. The report will include literature review, anatomy dissection, walking gait experiments and stimulation protocol.